Study of Malaysian-sized hand phantom for GSM900/1800 application - Ronald, Suzanna Harun; Mohd Fareq, Abd Malek, Dr.; Mohd Hafizuddin, Mat; Zulkefli, M. S. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/